2017
DOI: 10.15578/jra.12.1.2017.85-97
|View full text |Cite
|
Sign up to set email alerts
|

RESPON IMUNITAS BENIH LOBSTER, Panulirus homarus DENGAN PENGGUNAAN PROBIOTIK PADA PAKAN MOIST

Abstract: ABSTRAKPemeliharaan benih lobster P. homarus masih menghadapi beberapa permasalahan, di antaranya infeksi penyakit bakteri (red body disease) dan mortalitas yang tinggi. Tujuan penelitian ini adalah untuk mengkaji respons imunitas benih lobster P. homarus yang diberi pakan pelet basah (moist diets) dengan penambahan probiotik. Pemeliharaan benih lobster dilakukan secara individu (1 ekor/keranjang). Lama pemeliharaan selama tiga bulan. Bobot awal puerulus P. homarus adalah 0,37 ± 0,05 g. Perlakuan meliputi pemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Irrespective of diets, the survival of juveniles remained constant and was similar to that reported by Smith et.al ( 2003), but higher than the previously reported by (Haryanti et al, 2017;Smith et.al 2005). The individual rearing system used in the present study has successfully protected the lobster juvenile from cannibalism and also assisted in assessing moult rates and moult intervals of the individual lobsters.…”
Section: Amino Acidssupporting
confidence: 89%
“…Irrespective of diets, the survival of juveniles remained constant and was similar to that reported by Smith et.al ( 2003), but higher than the previously reported by (Haryanti et al, 2017;Smith et.al 2005). The individual rearing system used in the present study has successfully protected the lobster juvenile from cannibalism and also assisted in assessing moult rates and moult intervals of the individual lobsters.…”
Section: Amino Acidssupporting
confidence: 89%
“…The survival of juvenile lobsters in this study remained constant, which confirmed Smith et al (2003), but higher than that reported by Haryanti et al (2017). The individual rearing system used in this study successfully protected the juvenile lobsters from cannibalism and simplified the assessment of moult rates, moult intervals, and ADM of the juvenile lobsters.…”
Section: Discussionsupporting
confidence: 79%
“…Lobster hemolymph was taken in the ventral portion between the fourth and fifth walking legs by using a 1 mm syringe that is coated with EDTA as an anticoagulant (Atherley et al, 2020;Haryanti et al, 2017). The calculation of hemocytes was done by Hertika et al (2021) using a light microscope with 400 magnification.…”
Section: Total Hemocyte Count (Thc)mentioning
confidence: 99%